Is velocity-specific strength training important in improving functional performance? - Cronin, J. B.; McNair, P. J.; Marshall, R. N. (The Journal of Sports Medicine and Physical Fitness, 2002)
A variable considered when designing programs to optimize athletic performance is training velocity. It has been suggested that training at a specific velocity improves strength mainly at that velocity and as velocity deviates from the trained velocity, the less effective training will be. However, the research describing velocity-specific adaptation and the transference of these adaptations to other movement velocities is by no means clear. Compounding the problem in this area is the failure of research to detail the relationship between training velocity and actual movement velocity of a given task or athletic pursuit. In most cases there is a great disparity between training velocity and actual movement velocity. Factors that may better develop and explain velocity-specific adaptation in relation to functional performance are discussed. Developing qualities such as strength, power and rate of force development would appear of greater importance than training at the actual movement velocity of a task. It may be that irrespective of load and limb velocity, the repeated intent to move an isoinertial load as rapidly as possible might be an important stimulus for functional high velocity adaptation. The ability of the nervous system to activate and coordinate agonist, synergist and antagonist activity would seem essential. It was suggested training techniques that simulate the velocity and acceleration profiles associated with the desired functional performance, such as throw or jump training, may optimize functional adaptation. Furthermore combination training that incorporates same session sport specific training with either a heavy load or a mixed training load approach might provide an optimal strategy for promoting intramuscular and intermuscular co-ordination and improving functional performance.